A pilot randomised controlled trial of the feasibility of using body scan and isometric exercises for reducing urge to smoke in a smoking cessation clinic - Aveyard Paul; Stenner Sarah; Steed Lucy; Prasad Neha; Al-Chalabi Lemees; Beach Jane; Ussher Michael (BMC, 2008)
Abstract Background The main cause of relapse in smokers attempting to quit is inability to resist urges to smoke. Pharmacotherapy ameliorates but does not entirely prevent urges to smoke when abstinent, so other methods to resist urges to smoke might be helpful. Exercise is effective, but aerobic exercise is often impractical when urges strike. Two techniques, body scan and isometric exercise, have been shown to reduce urge intensity and nicotine withdrawal symptoms in temporarily abstinent smokers. It is unclear whether they would be used or effective in typical smokers attempting to quit. Methods In a pilot trial set in a UK smoking cessation clinic, 20 smokers were randomised to receive emails containing .mp3 files and .pdf illustrations of the instructions for doing the body scan and isometric exercises. Twenty smokers received no other intervention, although all 40 were receiving weekly behavioural support and nicotine replacement therapy. Carbon monoxide confirmed abstinence, nicotine withdrawal symptoms, urges to smoke, and use of the techniques to resist urges were recorded weekly for four weeks after quit day. Results 60-80% of quitters reported using the isometric exercises each week and 40-70% reported using the body scan to deal with urges. On average, these techniques were rated as 'slightly helpful' for controlling the urges. There were no large or significant differences in withdrawal symptoms or urge intensity between the two groups. The risk ratio and 95% confidence interval for exercises compared with controls for prolonged confirmed abstinence at four weeks was 0.82 (0.44-1.53). 81% of quitters intended to continue using isometric exercises and 25% body scan, while 81% and 50% respectively would recommend using these techniques to others trying to stop. Conclusion Isometric exercises, and to a lesser extent body scan, were popular and perceived as somewhat helpful by quitters. The trial showed that these techniques were used and a larger trial could now be developed to examine the influence of the methods on reducing urges to smoke and increasing abstinence. Trial registration ISRCTN70036823